La ecología profunda y el Popol Vuh - Naranjo, José Ramón (Anales de Literatura Hispanoamericana, 2004)
«Deep Ecology» represents a current of thought which surpasses the anthropocentric leaning of traditional ecological movements and brings into play the global dimension of the problem. The general systemic theory, the holonistic worldview and the GAIA hypothesis open unsuspected possibilities in the field of interdisciplinary research and permit a reading of the Popol Vuh from the analogy of its own revolutionary ideas. Even today, many of Spanish America’s ecological needs and impulses are structured around images or narratives taken from the mythical indigenous world and particularly from the Popol Vuh, the most important work of the mythical indigenous literature from the Mayan area. The unique myths of this ancient culture fashion in their literature a new encounter between the human being and an Earth which is seen as a living being, organically formed as a principle of biological, intelligent unity.